Microbial Eukaryotes in an Arctic Under-Ice Spring Bloom North of Svalbard - Meshram, Archana R.; Vader, Anna; Kristiansen, Svein; Gabrielsen, Tove M. (Frontiers in Microbiology, 2017)
Microbial eukaryotes can play prominent roles in the Arctic marine ecosystem, but their diversity and variability is not well known in the ice-covered ecosys-tems. We determined the community composition of predominantly picoflagel-lates in an Arctic under-ice spring bloom north of Svalbard using 454 pyrose-quencing of 18S V4 rRNA and the rRNA gene. At the two stations studied, the photosynthetic biomass was dominated by protists > 3µm and was concentrated in the upper 70-80 m, above the thermocline and halocline. Hierarchical cluster analyses as well as ordination analyses showed a distinct clustering of the mi-crobial eukaryote communities according to a combination of watermass and local environmental characteristics. While samples collected in the surface mixed layer differed distinctly between the two sites, the deeper communities collected in Atlantic Water were fairly similar despite being geographically distant. The differentiation of the microbial eukaryote communities of the upper mixed water was probably driven by local development and advection, while the lack of such differentiation in the communities of Atlantic Water reflects the homogenizing effect of water currents on microbial communities.